1991
DOI: 10.2527/1991.6972677x
|View full text |Cite
|
Sign up to set email alerts
|

Feedlot performance of Brahman × Angus versus Angus steers during cold weather

Abstract: Ten Angus and 10 Brahman x Angus F1 steers were used in a 184-d trial to compare feedlot performance during cold weather (-9 to 26 degrees C). Both groups of steers were exposed to the same environment for the same amount of time. All steers were fed for the same number of days regardless of frame score to avoid frame score x environment interactions. Brahman x Angus steers were 30.7 kg heavier (P less than .05) than Angus steers at the start of the trial. Differences in age (Brahman x Angus 40 d younger) for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 0 publications
2
5
0
Order By: Relevance
“…However, our data indicate that no difference exists in total tract OM digestibility between MARC III and Bos indicus × MARC III steers fed a high-grain diet. These results are supported by previous research with Bos taurus × Bos indicus crossbreds fed concentrate diets (Boyles and Riley, 1991;Colditz and Kellaway, 1972). In these experiments, total tract diet DM digestibility was similar between Bos taurus and Bos indicus × Bos taurus cattle.…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…However, our data indicate that no difference exists in total tract OM digestibility between MARC III and Bos indicus × MARC III steers fed a high-grain diet. These results are supported by previous research with Bos taurus × Bos indicus crossbreds fed concentrate diets (Boyles and Riley, 1991;Colditz and Kellaway, 1972). In these experiments, total tract diet DM digestibility was similar between Bos taurus and Bos indicus × Bos taurus cattle.…”
Section: Resultssupporting
confidence: 89%
“…Biological type did not affect (P > .05) daily gain, DMI, or gain:feed ratio. Similar to our experiment, Boyles and Riley (1991) found no difference in ADG or feed:gain in Angus vs Brahman × Angus steers consuming an 85% concentrate diet, and Kappel et al (1972) and Young et al (1978) reported no significant difference in feedlot performance among British and Zebu breed types. In contrast, other research demonstrated that greater DMI (Beaver et al, 1989;Huffman et al, 1990) and ADG (Adams et al, 1982;Carroll et al, 1955;Beaver et al, 1989) were achieved in British type cattle compared to Bos indicus-cross cattle consuming a high-grain diet.…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…The Brahman breed has been used extensively in the southern U.S. beef cattle herds to incorporate genetic adaptation to heat stress and to increase cow-calf enterprise productivity. However, when these calves are sold for finishing on high-concentrate diets in intensively managed feedlots, they are usually discounted due to poorer feedlot ADG (Phillips et al, 2001), lower marbling scores (Boyles and Riley, 1991;Phillips et al, 2001) and lower carcass quality (Sherbeck et al, 1996: Riley et al, 2003 as compared to steers with little or no Brahman breeding. The majority of the U.S. beef calves are born in winter or spring and weaned in the fall.…”
Section: Introductionmentioning
confidence: 99%